2021
DOI: 10.1002/vms3.573
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome analysis reveals potential mechanisms of the effects of dietary Enteromorpha polysaccharides on bursa of Fabricius in broilers

Abstract: The present study was conducted to evaluate the effects of dietary supplementation of Enteromorpha polysaccharides (EP) on relative organ weight of broilers, and RNA‐seq technique was used to reveal the potential molecular mechanisms of the positive effects of EP on relative organ weight. A total of 396 1‐day‐old male chicks (Arbor Acres) were randomly assigned to six dietary treatments containing EP at 0 (EP0), 1000 (EP1000), 2500 (EP2500), 4000 (EP4000), 5500 (EP5500), and 7000 (EP7000) mg/kg levels for a 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Besides, EP has been found to regulate intestinal microbiota in chicken ( Wassie et al, 2021b ), mice ( Zhang et al, 2018 ), and fecal microbiota in humans ( Kong et al, 2016 ). Qiu et al (2021) reported that supplementation of diet with EP enhances weight and differentially regulates the gene expression at the transcriptome level in the bursa of Fabricius of Arbor Acres chickens. Furthermore, our previous studies demonstrated that EP-zinc supplementation could improve intestinal health in piglets ( Xie et al, 2021 ), and regulate amino acid and fatty acid metabolism in chicken ( Wassie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, EP has been found to regulate intestinal microbiota in chicken ( Wassie et al, 2021b ), mice ( Zhang et al, 2018 ), and fecal microbiota in humans ( Kong et al, 2016 ). Qiu et al (2021) reported that supplementation of diet with EP enhances weight and differentially regulates the gene expression at the transcriptome level in the bursa of Fabricius of Arbor Acres chickens. Furthermore, our previous studies demonstrated that EP-zinc supplementation could improve intestinal health in piglets ( Xie et al, 2021 ), and regulate amino acid and fatty acid metabolism in chicken ( Wassie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated increased production performance, breast muscle yield, egg quality, antioxidant capacity, and intestinal morphology of chickens fed seaweed polysaccharides (15)(16)(17)(18). In addition, EP supplementation increased the weight and differentially regulates the gene expression at the transcriptome level in the bursa of Fabricius of Arbor Acres chickens (19).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated increased production performance, breast muscle yield, egg quality, antioxidant capacity, and intestinal morphology of chickens fed seaweed polysaccharides ( 15 18 ). In addition, EP supplementation increased the weight and differentially regulates the gene expression at the transcriptome level in the bursa of Fabricius of Arbor Acres chickens ( 19 ). Similarly, EP supplementation has been shown to improve the growth performance, non-specific immunity, and intestinal function of banana shrimp F. merguiensis fish ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides were also benefited to improve the T-lymphocyte percentage and enhance the development of immune organs, evidenced by the increased lymph follicle area in the bursa of Fabricius and white pulp area expansion, which suggested that polysaccharide treatment elicited lymphocyte formation in the bursa of Fabricius (36). Further study by transcriptome analysis revealed that dietary Enteromorpha polysaccharides regulated 20 differentially expressed genes of the bursa of Fabricius, which were mainly enriched in negative regulation of the Toll-like receptor signaling pathway and mainly enriched in phagosome, mitophagy-animal, Salmonella infection, and autophagy signaling pathways (34). Moreover, it was identified that algae-derived polysaccharides ameliorated the impairment of the bursa of Fabricius in heat-stressed broilers via modulation of the NF-κB signaling pathway (35).…”
Section: Immnune Organ and Serum Immunoglobulinmentioning
confidence: 95%
“…The reason for the higher activity of γ-irradiated APS was that irradiation leads to the cleavage of glycosidic bonds by electromagnetic waves of gamma rays and resulted in low molecular weight polysaccharide products, which affected their biological activities (9,32,33). Enteromorpha polysaccharide administration increased the relative weight of the bursa of Fabricius in broilers (34) and improved the morphology of the bursa of Fabricius, including infiltration of inflammatory cells, destruction of the cell structure, and cell necrosis (35). It has been demonstrated that Camellia oleifera cake polysaccharides increased the weight or index of the spleen and thymus of broilers (19).…”
Section: Immnune Organ and Serum Immunoglobulinmentioning
confidence: 99%